2012
DOI: 10.1177/000313481207800254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adenoma Detection Rates between Gastroenterologists and Colorectal Surgeons

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Our findings parallel other studies that found no significant differences for ADRs between specialties. Ollington et al[ 3 ] compared the ADR between gastroenterologists and colorectal surgeons in California. 180 and 119 colonoscopies were performed by 8 gastroenterologists and 16 colorectal surgeons respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings parallel other studies that found no significant differences for ADRs between specialties. Ollington et al[ 3 ] compared the ADR between gastroenterologists and colorectal surgeons in California. 180 and 119 colonoscopies were performed by 8 gastroenterologists and 16 colorectal surgeons respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The performances of gastroenterologists and colorectal surgeons in colonoscopy have been compared in the literature, with varied results. Several studies have demonstrated that gastroenterologists are more effective than non-gastroenterologists at preventing CRC by colonoscopy whilst other studies have showed no difference between the two specialties[ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like conventional adenomas, the risk for CRC among patients with SPs depends on the size, number, and the presence of dysplasia. Literature suggests that proximal SPs with larger size have an increased risk of malignant transformation [7]. A similar study pertaining to Adenomas in 2012 showed detection of adenomas among endoscopists who had longer mean times for withdrawal of the colonoscope [8].…”
mentioning
confidence: 94%